Characterizing fracture response of cracked transversely graded materials. (1st December 2019) - Koohbor, Behrad; Rohanifar, Milad; Kidane, Addis
Abstract: Property gradation along a crack front makes conventional fracture mechanics analyses challenging. This issue is addressed in the present study through a combination of full-field measurements and modeling. We develop a novel experimental setup that consists of a synchronous dual Digital Image Correlation (DIC) system, facilitating in situ measurement of displacement and strain fields on both sides of a transversely precracked multi-layered structure subjected to uniaxial tensile load. By measuring the evolution of stress intensity factors developed on the opposite sides of the sample, we explore the mechanisms of crack initiation and propagation in the examined graded sample. Our experimental measurements are supplemented by a finite element analysis that elucidates the deformation and fracture response of the internal layers for which surface measurement is not possible. Finally, based on experimental and numerical observations, we develop a simple model that allows for prediction of critical far-field loads at which transversely graded structures fail. The capability of our proposed model in predicting tensile failure loads is demonstrated through a brief study of the influence of gradient function on the load bearing and fracture resistance in various graded structures.